Asymptotic stability analysis for a class of systems in chemical process. (2015) - Liu, Xinghua; Xi, Hongsheng
Based on the two-stage dissolution tank in the chemical process, the certain and uncertain neutral systems with time-delay and saturating actuators are investigated in the paper. By the model transformation and the delay-dividing approach, new delay-dependent LMI conditions for asymptotic stability are obtained by Lyapunov method. Finally, from the two-stage dissolution tank of solid caustic soda in a chemical plant, numerical examples are provided to show that the proposed results significantly improve the allowed upper bounds of the delay size over some existing ones in the literature. It has important guidance functions to the chemical plant production control.